1999
DOI: 10.1097/00004647-199909000-00011
|View full text |Cite
|
Sign up to set email alerts
|

Adventitial Expression of Recombinant Endothelial Nitric Oxide Synthase Gene Reverses Vasoconstrictor Effect of Endothelin-1

Abstract: The present study was designed to determine the effect of recombinant endothelial nitric oxide synthase (eNOS) gene expression on reactivity of canine basilar arteries to endothelin-1 (ET-1). Experiments were performed ex vivo. The arteries were exposed (30 minutes at 37 degrees C) to adenoviral vectors encoding eNOS gene (AdCMVeNOS) or beta-galactosidase reporter gene (AdCMVbeta-Gal). Twenty-four hours after transduction, transgene expression was evident mainly in the vascular adventitia. Rings of control (no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
21
0

Year Published

2000
2000
2007
2007

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 12 publications
(25 citation statements)
references
References 42 publications
4
21
0
Order By: Relevance
“…[3][4][5][6] This observation was confirmed in the present study. In AdCMVS1179DeNOS-transduced arteries we detected high expression of recombinant protein by Western analysis.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…[3][4][5][6] This observation was confirmed in the present study. In AdCMVS1179DeNOS-transduced arteries we detected high expression of recombinant protein by Western analysis.…”
Section: Discussionsupporting
confidence: 92%
“…1,2 Previous studies demonstrated that the recombinant eNOS gene can be transferred with the use of adenoviral vectors into the adventitial layer of cerebral [3][4][5][6] and peripheral [7][8][9][10] arteries. The expression of eNOS gene in the adventitia can augment the vasodilator effect of bradykinin [3][4][5] and inhibit the vasoconstrictor effect of endothelin-1 (ET-1) 6 in canine cerebral arteries.…”
mentioning
confidence: 99%
“…A similar finding was reported in an ex vivo basilar artery gene transfer study by Onoue et al 6 who postulated that because activation of fibroblast ET A receptors causes increased intracytosolic calcium levels, ET-1 may stimulate recombinant eNOS (a calcium-activated enzyme) through an ET A receptor-mediated pathway, thereby facilitating NO production by adventitial fibroblasts and paradoxically protecting against contractions. It is therefore apparent that functional vasoprotection conferred by recombinant eNOS expression in AdeNOS-transduced arteries is mediated through both augmentation of relaxation and attenuation of contraction.…”
Section: Vasomotor Functionsupporting
confidence: 82%
“…T he expression and function of recombinant genes in cerebral arteries after adenovirus-mediated gene transfer have been extensively characterized, [1][2][3][4][5][6][7] although the ability of recombinant endothelial nitric oxide synthase (eNOS) gene expression to ameliorate a disease involving intracranial arteries has not been demonstrated. The present study, representing a continuation of efforts to translate cerebrovascular gene transfer technology closer to the clinical arena, 8 was performed to characterize this ability, particularly in view of the important role played by NO in normal vasomotor function and the pathogenesis of cardiovascular diseases, including post-subarachnoid hemorrhage (SAH) cerebral vasospasm.…”
mentioning
confidence: 99%
“…First, NO may be only one of a number of important mediators underlying the pathogenesis of cerebrovascular disease; other candidates include calcitonin gene-related peptide (CGRP), endothelin-1 (ET-1), and altered enzymatic activities of cyclooxygenase, superoxide dismutase (SOD), and heme oxygenase-1 (HO-1) (Chen et al, 1997a;De Belder and Radomski, 1994;Dietrich and Dacey, 2000;Furchgott and Zawadzki, 1980;Khurana and Besser, 1997;Luders et al, 2000;Ono et al, 2002;Onoue et al, 1998Onoue et al, , 1999Toyoda et al, 2000c;Vanhoutte, 1998; Human Pial (intact arteries) Adenovirus iNOS ex vivo Function * All animal disease models were related to subarachnoid hemorrhage (SAH) and post-SAH cerebral vasospasm, with the exception of the study by Lund et al (1998), in which the disease model was atherosclerosis.…”
Section: Genesmentioning
confidence: 99%